Validation of trap density theory in single layer organic light emitting diodes with tris(8 hydroxyquinolinato)aluminium as the emissive material / Mohd Suffian Zaini - Mohd Suffian , Zaini (2020)
Organic light-emitting diodes (OLEDs) rapidly evolving as the future of solid-state lighting and display application due to its numerous advantages and features. However, the efficiency, lifetime, and fabrication method still need to be improved. Even in solving efficiency issues in the device, there are many challenges to be addressed and overcome. In theory, charge transport phenomena contribute greatly towards increasing or improving the device efficiency. The magnitude of carrier mobility determines the performance of the device, as it influenced device efficiency. For organic semiconductor such as OLED, space-charge limited current (SCLC) theory was used to determine the mobility of the device. This theory is often true for a very basic structure in a simple organic semiconductor. One of the weaknesses in SCLC theory is that traps phenomena or trap density is neglected and not considered in formulating the mobility of charge carrier. In this thesis, a theoretical model for single-layer OLED that includes trap density is explained with the help of an equation. The focus of this thesis is to analyze and discussed the trap density effect in a single layer OLED. A single layer emissive OLED is fabricated for this project in order to validate the theory presented. Tris(8-hydroxyquinolinato )aluminium (Alq3) is chosen as the emissive material since it has been researched widely, and much-needed parameters can be easily obtained from previous research. The trap density value obtained at voltage 14 V when OLED A luminesces is 2.40 × 1015 cm-3. It is comparable with other results that have been reported indicating the method used is reliable. The rate of capturing process (trapping), Rn and de-trapping, Rn’ of the charge carriers on the localized state of the device are estimated. The parameters Rn and Rn' are plotted on the same graph to observe their relationship with the luminescence of the device. It can be observed that there are two significant regions in the plot, Rn > Rn’ and Rn < Rn’, and the intersection point of Rn with that of Rn’ indicate the voltage at which the device luminesces or known as the turn-on voltage of the device. Simulations are then performed by directly increasing the device trap density by two-fold to that of OLED A. The simulation has indicated that trap density has a strong influence on the Rn and Rn’ parameters. In order to verify the finding of the simulation, another device (OLED B) with a hole transport layer (HTL) of Poly(N,N’-bis-4 butylphenyl-N,N’-bisphenyl) benzidine (poly-TPD) of 40 nm thickness is fabricated by adding the HTL layer to the existing structure of that of OLED A. It has been proven in this work that OLED B, having a higher value of trap density luminesces at a much lower turn-on voltage, as has been predicted by the simulation results due to the influence of trap density to the parameters of Rn and Rn’ of the devices.